Persistent Atmospheric and Ecosystem Impacts of Enteric Methane Emissions from Intensive Livestock Production Systems - Md. Emran Hossain (International Journal of Atmosphere, 2025)
Enteric methane emissions from intensive livestock production systems exert a significant long-lasting influence on atmospheric stability and ecosystem integrity. Recent observations confirm that global methane emissions continued to rise through the early 2020s, with total emissions exceeding 620 teragrams per year by 2024, driven by expanding ruminant production and associated feed systems. Anthropogenic sources accounted for more than 330 teragrams per year, reflecting sustained growth in agricultural and fossil fuel sectors. Enteric fermentation alone contributed an estimated 140 teragrams per year by 2023, representing a continued upward trend linked to intensification of dairy and beef operations. These escalating emissions have amplified atmospheric methane concentrations, reaching approximately 1960 parts per billion in 2025, substantially above levels recorded in previous decades. Annual methane growth rates from 2021 to 2025 remained elevated compared with early-2000s averages, indicating persistent perturbations of atmospheric composition. Methane-driven changes in hydroxyl radical abundance and consequent effects on tropospheric ozone formation illustrate disruptions to atmospheric chemical stability that extend beyond greenhouse forcing. The consequences of increasing methane burdens extend into terrestrial ecosystems. Although global soil organic carbon stocks remain substantial, localized declines of 5 to 20 percent have been documented in regions subject to intense grazing pressure, elevated manure inputs, and accelerated erosion. These losses underscore pressures on ecosystem integrity where biological processes fail to offset disturbances. Meanwhile, global land use and land cover change continue to support a net carbon dioxide sink near 1.5 to 1.7 gigatonnes per year, yet this sink has weakened in zones experiencing high warming rates, reduced precipitation, and deforestation. This review synthesises the latest quantitative evidence on the biological mechanisms of enteric methane production, the characteristics of intensive livestock systems, and the atmospheric pathways through which methane alters climatic and chemical stability. It evaluates ecosystem-level responses involving vegetation composition, nutrient cycling, hydrological balance, and biodiversity change. Feedback linking rising temperatures, shifts in feed quality, rumen microbial adaptation, and secondary greenhouse gas emissions are examined. Key measurement challenges, including uncertainties in tracer and chamber methods and data gaps in under-sampled regions, are critically assessed. Finally, mitigation strategies across nutritional, genetic, microbial, and management domains are reviewed, with emphasis on trade-offs and approaches to enhance climate resilience and environmental integrity for healthy atmosphere.
Keywords: Atmosphere; Climate change; Mitigation strategies; enteric methane; intensive livestock; methanogenesis